Child stunting prevention: The challenge of mobilizing local governments for national impact - Alejandro N. Herrin; Michael Ralph M. Abrigo; Zhandra C. Tam; Danica Aisa P. Ortiz (Philippine Institute for Development Studies (PIDS), 2018)
Key to achieving national targets under a devolved set-up is the capacity of the entire system to implement health and nutrition programs at scale. This requires coordinated efforts among the Local Government Units (LGUs) with the same energy and commitment. Though still few relative to the total number of LGUs, there are LGUs that have demonstrated that they can meet the challenge of implementing a number of nutrition-related interventions in a sustained matter. Moreover, while past interventions were focused to large extent on feeding programs for older children in Day Care Centers and schools, there is increasing interest in implementing the First 1,000 Days Program. There are also LGUs that, with training in leadership and governance, can facilitate improvements in their local health system that involve inter-LGU among province, municipality and city LGUs to deliver a continuum of maternal, neonatal and child health care in a service delivery network. Based on the experiences of these LGUs, it is possible to move forward by systematically addressing two sets of issues: one of governance and health systems improvements; and two of strengthening key elements and filling out gaps in existing maternal, neonatal and child health and nutrition programs, particularly the nutrition-specific components.
Keywords: 330; stunting; maternal and child care; local governance; first 1; 000 days; child health and nutrition